Body condition of gray whales (Eschrichtius robustus) feeding on the Pacific Coast reflects local and basin-wide environmental drivers - Akmajian, Adrianne M; Scordino, Jonathan J; Gearin, Patrick J; Gosho, Merrill (J. Cetacean Res. Manage., 2021)
A small subset of the Eastern North Pacific gray whale population does not make the full migration from wintering grounds in Mexico to feeding grounds in the Bering, Chukchi and Beaufort seas and instead feed along the Pacific Coast between northern California and northern British Columbia – this group is known as the Pacific Coast Feeding Group (PCFG). We evaluated the body condition of PCFG whales observed in northern Washington and along Vancouver Island to evaluate how body condition of gray whales changes within and between years. We found that PCFG gray whales improve body condition through the feeding season and at varying rates by year and that they have variability in their body condition at the start and end of each feeding season. The inclusion of environmental factors, particularly the Pacific Decadal Oscillation (lagged two years) and September kelp canopy cover along the Washington coast (lagged one year), drastically improved the ability of a multiple regression model to predict average whale body condition for a given year as compared to models without environmental factors included. A comparison of our findings to a previously published study on body condition of gray whales at Sakhalin Island, Russia highlight the differences of life history strategy between a group of whales with a long migration (Sakhalin whales) and those with a short migration. Whales feeding at Sakhalin Island gain body condition quicker and more predictably to a good body condition by the end of the feeding season than the whales we studied in the PCFG. Photogrammetry may be an effective method for monitoring the effects of climate change on PCFG gray whales.